Urgensi dan Legitimasi Fatwa Majelis Permusyawaratan Ulama Aceh Nomor 3 Tahun 2018 tentang Penetapan Arah Kiblat - Ismail, Ismail (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
When Muslims have settled on the earth, one of the problems which become a focus of attention is the Kiblah direction. For Muslims, the Kiblah direction is not only the need for prayer which is one of the legitimate conditions of prayer, but also includes other needs related to Kiblah such as the position of burying the body, establishing a mosque and musalla. This paper explains the position of the MPU Aceh’s fatwa Number 3 of 2018 concerning the determination of the direction of the MUI of the fatwa of MUI number 3 and 5 of 2010 concerning the direction of Kiblah and explaining its relevance to the context. With the approach of astronomy, the position of the MPU Aceh fatwa Number 3 of 2018 concerning the determination of the direction of Kiblah is complementary to the MUI fatwa Number 3 and 5 of 2010 concerning the Kiblah direction. Improvements to the integrity and intensity of fatwas are responsive, proactive and anticipatory. The presence of the MPU Aceh’s fatwa on Kiblah direction is able to solve the problem of Kiblah direction in Indonesia, both in the technical and the sociological domain, because the content of the fatwa is relevant with the context and it accommodates the dimensions of science, technology and Fiqh as a characteristic of collective diligence (Ijtihad Jama'i).